Measuring Leukocyte Adhesion to (Primary) Endothelial Cells after Photon and Charged Particle Exposure with a Dedicated Laminar Flow Chamber - Erbeldinger, Nadine; Rapp, Felicitas; Ktitareva, Svetlana; Wendel, Philipp; Bothe, Anna S.; Dettmering, Till; Durante, Marco; Friedrich, Thomas; Bertulat, Bianca; Meyer, Stephanie; Cardoso, M. C.; Hehlgans, Stephanie; et al. (Frontiers in Immunology, 2017)
The vascular endothelium interacts with all types of blood cells and is a key modulator of local and systemic inflammatory processes, for example in the adhesion of blood leukocytes to endothelial cells (EC) and the following extravasation into the injured tissue. The endothelium is constantly exposed to mechanical forces caused by blood flow, and the resulting shear stress is essential for the maintenance of endothelial function. Changes in local hemodynamics are sensed by EC, leading to acute or persistent changes. Therefore, in vitro assessment of EC functionality should include shear stress as an essential parameter. Parallel-plate flow chambers with adjustable shear stress can be used to study EC properties. However, commercially available systems are not suitable for radiation experiments, especially with charged particles, which are increasingly used in radiotherapy of tumors. Therefore, research on charged-particle induced vascular side effects is needed. In addition, α-particle emitters (e.g. radon) are used to treat inflammatory diseases at low doses. In the present study, we established a flow chamber system, applicable for the investigation of radiation induced changes in the adhesion of lymphocytes to EC as readout for the onset of an inflammatory reaction or the modification of a pre-existing inflammatory state. In this system, primary human EC are cultured under physiological laminar shear stress, subjected to a pro-inflammatory treatment and/or irradiation with X-rays or charged particles, followed by a co-incubation with primary human lymphocytes (PBL). Analysis is performed by semi-automated quantification of fluorescent staining in microscopic pictures. First results obtained after irradiation with X-rays or helium ions indicate decreased adhesion of PBL to EC under laminar conditions for both radiation qualities, whereas adhesion of PBL under static conditions is not clearly affected by irradiation. Under static conditions, no radiation induced changes in surface expression of adhesion molecules and activation of NF-κB signaling were observed after single cell based high throughput analysis. In subsequent studies, these investigations will be extended to laminar conditions.